2004
DOI: 10.1073/pnas.0401960101
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin IV regulates glial glutamate release

Abstract: Calcium-binding synaptotagmins (Syts) are membrane proteins that are conserved from nematode to human. Fifteen Syts (Syts I-XV) have been identified in mammalian species. Syt I has been well studied and is a candidate for the Ca 2؉ -sensor that triggers evoked exocytosis underlying fast synaptic transmission. Whereas the functions of the other Syts are unclear, Syt IV is of particular interest because it is rapidly up-regulated after chronic depolarization or seizures, and because null mutations exhibit defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
170
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(181 citation statements)
references
References 56 publications
(73 reference statements)
11
170
0
Order By: Relevance
“…46,47 Despite the lack of Ca 2+ binding by the Syt IV and Syt XI C2A domains, 46 Syt IV facilitates regulated exocytosis in neurons, astrocytes and endocrine cells. 28,[48][49][50] Similarly, Syt XI-containing vesicles undergo depolarization-triggered exocytosis in neurons. 42 Similar to neuronal lysosomes, 51 Syt XI-containing exocytic vesicles in neurons are acidic in nature and localize to dendrites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…46,47 Despite the lack of Ca 2+ binding by the Syt IV and Syt XI C2A domains, 46 Syt IV facilitates regulated exocytosis in neurons, astrocytes and endocrine cells. 28,[48][49][50] Similarly, Syt XI-containing vesicles undergo depolarization-triggered exocytosis in neurons. 42 Similar to neuronal lysosomes, 51 Syt XI-containing exocytic vesicles in neurons are acidic in nature and localize to dendrites.…”
Section: Discussionmentioning
confidence: 99%
“…28 Whereas all these synaptotagmins showed punctate expression, only Syt XI colocalized with lysosomes (Figures 4a and b). Syt XI is the most abundant Syt isoform in astrocytes and is expressed more abundantly in the astrocytes as compared with the neurons; 27,28,30 however, its subcellular localization in astrocytes is not known. 41,42 Use of western blot analysis confirmed expression of Syt XI protein in primary astrocytes (Figure 4c).…”
Section: Syt XI Regulates Lysosomal Exocytosis In Astrocytesmentioning
confidence: 95%
See 1 more Smart Citation
“…SYT IV, SYT VII and REST silencing vectors Specific small interfering RNA (siRNA) were designed as follows: for rat Syt4, the sense target sequence 5′GAAGCACAAAGT GAAAACCA3′ was deduced from the reported mouse sequence [18]; for rat Syt7 the sense sequence 5′TCAT CACCGTCAGCCTTAG3′ was selected according to a previous publication [19]; for REST, the sense sequence 5′ GGAACCTGTTGAGAAGGGA3′ was selected using the siRNA Target Finder (Ambion, Austin, TX, USA). Two complementary DNA fragments encoding the target sequence and separated from the reverse complement by a short spacer were synthesised by Microsynth (Balgach, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…They generated a transgenic mouse with astrocytic over-expression of a dominant-negative form of synaptobrevin-2, which largely abrogates exocytotic release selectively from astrocytes (Zhang et al, 2004). They found that this lead to the disappearance of the tonic A 1 receptor-mediated inhibition on synaptic transmission in hippocampal slices (Pascual et al, 2005).…”
Section: Source Of Endogenous Extracellular Adenosinementioning
confidence: 99%